Exceptional points in a topological waveguide-cavity coupled system - Junhua Dong; Qingmei Hu; Chang-Yin Ji; Bingsuo Zou; Yongyou Zhang (New Journal of Physics, 2021)
Exceptional points (EPs) as branch singularities describe peculiar degeneracies of non-Hermitian systems, widely studied in topological and non-topological optical architectures with introducing gain or loss technically. This work focuses on the EPs in a topological waveguide (TW)-cavity coupled structure, where there is no need to introduce practical gain or loss. The topological cavity contains two degenerate counter-propagation topological whispering gallery modes, whose coupling with the TW leads to the effective gain and loss, responsible for the EP. Such a photonic architecture is designed practically by crystal-symmetry-protected topological photonic insulators based on air rods in conventional dielectric materials. The relevant EP reveals the breaking of the parity-time symmetry, reflected by the change of the transmission-dip number in the optical transmission spectra of the system. Achieving EPs in topological photonic systems possibly opens a new avenue toward robust optical devices with exceptional-point-based unique properties and functionalities.